Stability analysis using the finite element method of a slope in the Virgen de Fátima Sector of the San Juan de Lurigancho district of Lima, Peru - Carrizales, N. (2022)
The geometric alteration of slopes is a reality that can be observed in several districts of the Peruvian capital. The construction of houses, roads, and other infrastructure can produce some slope instability and cause tragic events. Thus, a stability analysis was carried out for a slope located in the San Juan de Lurigancho district, specifically in the Virgen de Fátima sector. Therefore, for the present investigation, two models were made with the help of Phase2 software to identify the resistance reduction factors (SFR), which is a finite element-based program. To start the analysis, possible failures were identified, demonstrating that the slope does not present any possibility of failure. For the first model, we worked with a dip of 30° and identified an SFR = 19.26 for static conditions and an SFR = 9.66 for pseudo-static conditions. For the second model, we worked with a dip of 55°, this change in slope geometry shows a possible wedge failure, according to the kinematic analysis. Also, an SFR = 0.89 was identified for static conditions and an SFR = 0.48 for pseudo-static conditions. The results show very considerable changes and are due to the geometry of the slope, the presence of discontinuities, and the participation of seismic forces.